O discurso dos docentes sobre projetos ambientais empresariais na escola - Ferreira, Dalila de Souza (2015)
In this paper, we analyze how business projects act for Environmental Education school and how teachers understand these projects. Therefore, we focused on three business environmental projects working in the public schools of the city of Uberlândia: De grão em grão, Municípios Canavieiros and Reciclou, Ganhou. A more detailed analysis in this study on the contribution of companies with the school EA, and specifically with the continuing education of teachers was made possible by the project Municípios Canavieiros, as this provides on its site the teacher\'s notebook delivered to participating schools. It was used as a methodological resource discourse analysis in the material disclosure of business projects: websites, teacher\'s notebook, multimedia kits, videos; trying to understand some aspects: development of Environmental Education in school, what subjects responsible for project development, as teacher training to work in these projects, the age group of students that the project covers performance period in schools, resources that the company provides the school. Later offer a workshop for teachers from different areas in order to aid understanding of the partnership company / school, and we did a focus group where teachers positioned themselves, exposing knowledge of this partnership, knowledge about the three projects concerned, positives and negative projects, continuing education activities for these projects, understanding of the contribution of these projects for school Environmental Education. It was possible to draw a counterpoint to the business representation and its environmental discourse with the narratives of the teachers who experienced projects undertaken by companies. So we outline a critical position, believing contribute to education professionals, as the school needs autonomy in the preparation, implementation and monitoring of environmental projects, breaking an imposed education and allowing no dialogue, growth and context.